Socio-Economic Impact on Participation in Decision Making of Husbands and Wives in Pakistan - Gondal, Amtul Hafeez (Economic Journal of Nepal, 2014)
which determine the labor force participation (LFP) decision of currently married husbandsand wives together in Pakistan. The sample size comprises of 14030 husbands and wivescurrently living together, excluding widows and divorced cases, and also both areparticipating in economic activities. The study uses Probit model in order to empiricallyidentify the effect of various social, economic and demographic factors like education, age,family structure and size, number of children and other household workers on LFP ofhusbands and wives. Education level is found to be strong determinant of their LFP decision.Joint family system, presence of small children, other household workers, household size andresidential province are positively and significantly related to it. The Economic Journal of Nepal, Vol. 34, No. 4, October-December 2011 (Issue N0. 136)